Turn Taking used in Conversation Class: A Classroom Discourse Analysis - Sa?adah, Lailatus; Yulianti, Rani (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2018)
This paper aimed to analyze the turn taking used by the teacher and students in conversation class and provide the authentic evidence of the classroom discourse. The script of conversation were chosen as the materials of the study. The analysis of turn taking is adopted from Sinclair and Coulthard?s framework (1975, cited in Christie, 2002) of IRF (Initiation, Response, Feedback) and Mehan?s work (1979, cited in Rymes, 2008) who proposed IRE (Initiation, Response, Evaluation). The underlying structure of the pattern is: (a) Teacher question or Initiation, (b) Student Response, and (c) Teacher evaluation or feedback (Bloome, et.al 2005).